PEMINDAHAN EMBRIO KE RAHIM WANITA LAIN DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Ashar, Ashar (Mazahib, 2015)
This article discusses the legal status of a child born from an embryo transfer from a woman who donors the egg to another woman who provide the womb. From Islamic law perspective, a child born from embryo transfer to another woman's womb belongs to the mother who gave birth to her, even though the egg is not from her. This then impacts on the inheritance status whereby the child can inherit from the mother who gave his/her birth, and vice versa. Meanwhile, positive law regards the child is the legal heirs of the parent who have the seed because they are the legal parent of the child pursuant to the agreement that has been agreed by the parties